2021
DOI: 10.1002/ecs2.3660
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the fattest: linking body condition to prey availability and survivorship of killer whales

Abstract: Recovering small, endangered populations is challenging, especially if the drivers of declines are not well understood. While infrequent births and deaths may be important to the outlook of endangered populations, small sample sizes confound studies seeking the mechanisms underlying demographic fluctuations. Individual metrics of health, such as nutritive condition, can provide a rich data source on population status and may translate into population trends. We examined interannual changes in body condition me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Body condition, defined as the amount of energy reserves relative to structural size, is a physiological unit of considerable interest in conservation-focused bioenergetic studies. As the physical manifestation of energy balance, body condition provides essential information about the health of individuals and populations ( Brock et al, 2013 ; Williams et al, 2013 ; Christiansen et al , 2020 ; Raverty et al , 2020 ; Stewart et al , 2021a ). A variety of metrics have been developed to estimate body condition of free-ranging marine mammals, such as those derived from blubber measures, morphometrics, biochemical or chemical markers, body composition and omics (see reviews in Bowen and Northridge, 2010 ; Castrillon and Bengtson Nash, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Body condition, defined as the amount of energy reserves relative to structural size, is a physiological unit of considerable interest in conservation-focused bioenergetic studies. As the physical manifestation of energy balance, body condition provides essential information about the health of individuals and populations ( Brock et al, 2013 ; Williams et al, 2013 ; Christiansen et al , 2020 ; Raverty et al , 2020 ; Stewart et al , 2021a ). A variety of metrics have been developed to estimate body condition of free-ranging marine mammals, such as those derived from blubber measures, morphometrics, biochemical or chemical markers, body composition and omics (see reviews in Bowen and Northridge, 2010 ; Castrillon and Bengtson Nash, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the focus here is on bioenergetic pathways, relationships between body condition and vital rates may thus incorporate the effects of non-bioenergetic pathways as well. In marine mammals, body size and condition metrics are positively related to foetal growth ( Christiansen et al, 2014b ), pregnancy rates ( Williams et al, 2013 ; Smout et al, 2020 ), offspring growth ( Christiansen et al, 2018 ) and survival probability ( Hall et al, 2001 ; Beauplet et al, 2005 ; Harding et al, 2005 ; McMahon and Burton, 2005 ; Bowen et al, 2015 ; Cheney et al, 2018 ; Oosthuizen et al, 2018 ; Stewart et al, 2021a ). For most marine mammals, these relationships and thresholds of body condition that equate to failed reproduction or imminent mortality remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model predicted that the SRKW population has been in energetic deficit for six of the last 40 years, notably from 2018 to 2020. Several previous studies have highlighted positive correlations between Chinook salmon abundance and SRKW body condition [ 73 ], survival rate [ 39 ], and fertility [ 40 ]. Although our analysis did not permit to support those findings with certainty, our model suggests that SRKW could have a higher birth rate and net population and a lower mortality rate in years during which their DPER was met.…”
Section: Discussionmentioning
confidence: 99%
“…nutritional status) of a range of species, particularly in marine environments (e.g. Pirotta et al 2017;Allan et al 2019;Stewart et al 2021a). Recent advances have shown that the precision of photogrammetric methods can be dramatically improved using deep learning, reducing the amount of time spent inputting information manually, which will facilitate expansion and development of photogrammetric methods to automatically measure individual animals with the greatest precision (Gray et al 2019).…”
Section: Looking Aheadmentioning
confidence: 99%